Gasteroid mycobiota (Agaricales, Geastrales, and Phallales) from Espinal forests in Argentina - Hernández Caffot, María Luciana (2015)
Sampling and analysis of gasteroid agaricomycete species (Phallomycetidaeand Agaricomycetidae) associated with relicts of native Espinal forests in the southeast region of Córdoba, Argentina, have identified twenty-nine species in fourteen genera:Bovista (4), Calvatia (2), Cyathus (1), Disciseda (4), Geastrum (7), Itajahya (1),Lycoperdon (2), Lysurus (2), Morganella (1), Mycenastrum (1), Myriostoma (1),Sphaerobolus (1), Tulostoma (1), and Vascellum (1). The gasteroid species from the sampled Espinal forests showed an overall similarity with those recorded from neighboringphytogeographic regions; however, a new species of Lysurus was found and is briefly described, and Bovista coprophila is a new record for Argentina.